Improvement of Growth Rate in In Vitro Culture of Paphiopedilum primulinum M. W. Wood and P. Taylor and Paphiopedilum glaucophyllum J. J. Smith using Banana Enrichment Media - Safitri; Dyah Carinae Yalapuspita; Elizabeth Handini; Popi Aprilianti; Yupi Isnaini; Endang Semiarti (Tropical Life Sciences Research, 2024)
Paphiopedilum primulinum and Paphiopedilum glaucophyllum have unique labellum colour and shaped like lady’s slippers. These orchids are from the Cochlopetalum section, which is exclusively found in Sumatra and Java. There are so many people that desire to collect these plants illegally. Due to extensive commercial exploitation, Paphiopedilum is in danger of going extinct. Tissue culture techniques are utilised to conserve threatened orchid germplasm in a short time. The success of the in vitro culture depends on the accuracy of the basic media composition used. The Ambon Lumut banana (ALB) can accelerate plant growth and cell division. Banana added to the culture medium was prepared by mashing the ripe flesh (3.5 months old) using a mortar. This research aims to investigate the effect of banana homogenate supplemented media for the orchids P. primulinum and P. glaucophyllum based on the parameters of difference of plant height (calculated from the base of the stem to the tip of the plant stem), number of leaves and number of roots. The measurement method was carried out using a ruler with a centimetre scale. Observations and documentation were carried out once a week for 7 weeks after planting (WAP) for P. primulinum and P. glaucophyllum. The results showed that ½ Murashige and Skoog (MS) + ALB homogenate is a better medium for P. primulinum and P. glaucophyllum growth than media without banana homogenate. The highest values of plant height, leaf growth, and root growth of P. primulinum with banana homogenate were 0.44 cm, 0.63 leaves and 0.50 roots, respectively. The highest values of plant height and leaf growth of P. glaucophyllum were 0.75 cm and 1.90 leaves, respectively. Culture medium added banana homogenate was able to support the propagation of plants, some of which are returned to nature and others used for industrial purposes (conventionally cultivated by the community).